PERANAN 3D AXIAL HYPERCUBE T2 FAT SAT PADA PEMERIKSAAN MRI PELVIS DENGAN KASUSU FISTULA PERIANAL - Nur’aini, Istiqomah; Iman, Nuzul; Serfina Fajarini, Eunike (Perhimpunan Radiografer Indonesia (PARI), 2020)
Background: Fistula is an abnormal relationship between two berepitel places. Fistula ani is a fistula that connects the anal canal to the skin around the anus (or to other organs such as the vagina). Magnetic Resonance Imaging (MRI) Pelvis is one of the right modalities to describe anatomical abnormalities of the pelvis, with the selection of appropriate protocol sequences so that informative MRI images are obtained. Method: This research is a qualitative detiptive study using a sample of 5 patients, with the same complaints, there are lumps such as ulcers in the anus area and there are eyes that secrete fluids such as pus and without a previous medical history. Mri Pelvic examination without contrast using MRI 1.5 Tesla Signa Explorer GE brand in Radiology RS EMC Tangerang. Taking a T2 axial sekuen to see the entire pelvis. Focus on perianal fistula area with sagittal sekuen T2, sagittal T2 fat sat, axial T2, axial T2 fat sat, coronol T2, coronal T2 fat sat and 3D axial hypercube T2 fat sat. Results: Sagittal T2 fat sat, axial T2 fat sat, and coronal T2 fat sat appear anatomically from perianal fistula and other abnormalities around them. In 3D axial hypercube T2 fat sat obtained anatomical picture of perianal fistula with thinner slice thickness. Conclusion: Mri Pelvis without contrast is a very accurate diagnostic imajing in showing perianal fistula abnormalities with a clear anatomical picture, is a non-inspative examination. Uses axial T2 sekuen for the entire pelvis. Sagittal T2, sagittal T2 fat sat, axial T2, axial T2 fat sat, coronal T2, coronal T2 fat sat, 3D axial hypercube T2 fat sat focus on perianal fistula area.